Universally Recognized International Legal Principles and Norms and International Treaties as Part of the Legal System of the Republic of Kyrgyzstan - B. D. Kadyralieva (Московский журнал международного права, 2007)
According to para. 3 art.12 of the Law of the Republic of Kyrgyzstan “About the New Edition of the Constitution of the Republic of Kyrgyzstan” international treaties and agreements of Kyrgyzstan and universally recognized international legal principles and norms are an integral part of the legal system of the Republic of Kyrgyzstan.In this respect it is necessary to mention that legal system should not be mistaken with the legislative system, as the legislative system means the total sum of national legal norms including constitutional norms, legal norms, etc. Thus it seems logical that in the abovementioned law international treaties and universally recognized international legal principles and norms are named as a part of the legal and not legislative system of Kyrgyzstan, as it had been before – in the previous Constitutions of the Republic of Kyrgyzstan.In the framework of the legal system of Kyrgyzstan “universally recognized international legal principle” means the jus cogens rule, which is binding on the states, and deviation from this rule is impossible. As for “universally recognized international legal norm”, it is a legally binding rule, which had been accepted by the international community of states.It is also necessary to differentiate “international treaty” which has a generic character and “international agreement” which is a specific name.Thus their legal effect is equal and the fact that they are used simultaneously in the text of the constitution of Kyrgyzstan is illogical. The differentiation between “international treaty” and “international agreement” shall not have any legal consequences in the framework of the legal system of Kyrguzstan.In the conclusion it is illustrated on several examples and proved that that in case of the legal system of Kyrgyzstan it is of crucial importance to draw up legal mechanisms of national implementation of international legal norms.